Entrepreneurial inclination on the level of firm performance - Abdul Majid, Izaidin; Ismail, Kamariah; Cooper, Sarah (2009)
There has been a lot of interest and effort made by many scholars to establish clear distinction between entrepreneurs and non-entrepreneurs, and also between entrepreneurial firms and non-entrepreneurial firms. Entrepreneurs were perceived, by virtue, as having superior decision-making abilities and thus, were able to create firms with the ability to generate high levels of profit and growth. On the other hand, small owner-managers and self-employed who may own capital may not have the same abilities or potential. This study explores the macroeconomic context of the technology-based firms operating in the Malaysian Multimedia Super Corridor (MSC) which was based on various secondary data available in the Multimedia Development Corporation’s (MDC) official website as well as primary data collected via survey. As anticipated, the analysis reveals that a larger percentage of firms with high entrepreneurial propensity were high performers, whereas a larger percentage of firms with low entrepreneurial propensity were low performers.